MAKNA PUISI DALAM ANTOLOGI PUISI â€œNUR EIN DUFT UND WINDESWEGENâ€ KARYA HERMANN HESSE (ANALISIS SEMIOTIKA RIFFATERRE) - CAHYA NINGSIH, DWI (IDENTITAET, 2016)
The purpose of this study was to find out the meaning which is contained in the ten poems about life. The poems are included in the anthology poem of ' Nur ein Duft und Windeswegen ' by Herman Hesse. This study used a semiotic analysis Riffaterre, reading heuristic, hermeneutic and indirect analysis expression, including the displacing of meaning, the distorting of meaning, and the creating of the meaning of the ten poems. The method that is used in the analysis is a descriptive qualitative method. The method utilizes interpretation ways and represents them in a description. The result of this study showed that there are similarities of core meaning between reading with a heuristic and hermeneutic in the ten poems. Since, in the ten poems are found a similarity usage of the figure of speech and connotations of words such as, ' die Blüte, die Welt, der Baum, and der Raum '. The result of whole analysis have a common core meaning of details of a person in the world. Within each title of poems, the poet describes the life condition in different ways, but it has the same core meaning.   Keywords: poetry anthology, Hesse, Hermeneutic, Heuristics